PROVIDERS PERSPECTIVE ON HWSETA ACCREDITATION SYSTEM AS PART OF QUALITY ASSURANCE - ZULU, BHEKI KENNETH (My University, 2011)
The accreditation of education and training providers by the Health and Welfare Sector Education and Training Authority (HWSETA) has occurred at a slow pace. The inaccessibility of the accreditation system has been regarded by many individuals as the main obstacle. The purpose of this study was to investigate how small providers experienced the accreditation system set up by the HWSETA and whether the attainment of accreditation resulted in any benefits and improvements for these providers. One of the main findings of the research shows that the providers found accreditation difficult and cumbersome, although there are benefits such as staff development and becoming credible institutions that were gained through this exercise. The language used in accreditation documentation and the length of the process of accreditation are the main factors that frustrated the providers whilst the provision of assistance and empowerment opportunities are viewed as factors that rendered accreditation achievable and worthwhile
MM - P&DM
Keywords: Quality assurance; Accreditation; Health and welfare sector education and training authority; Setas